Harmonization between Islamic law and science: DNA test of paternity as a case study - Haneef, Sayed Sikandar Shah (International Islamic University Malaysia, 2015)
DNA testing of paternity has emerged as a conclusive scientific evidence of as- certaining paternity to overcome the problem of ‘paternity fraud’ and ‘misattributed paternity’ in the West. To harmonize it with old established common law principles of ‘presumption of paternity` and ‘ex parte’ judgment for granting a woman her claim that her bastard child belongs to a certain accused, the Western legal system has accommo- dated it within its law of evidence. In Islamic law, on the other hand, its reception as conclusive evidence in establishing or negating paternity is a matter of controversy among the jurists. Some have approved it partially others advocate its wholesale adop- tion. This presents another interesting case for the issue of harmonization between Islam and science. In this divided juridical landscape, therefore, a selective approach to evi- dence and proof would regard it in total harmony with Islamic law. But this approach will not only be questionable on methodological grounds but also polemical in terms of social acceptability. This paper argues for regulated proof-based approach to address its harmonization with Islamic law.